Stitching through Silence: Walking With Our Sisters, Honoring the Missing and Murdered Aboriginal Women in Canada - Anderson, Stephanie G. (TEXTILE, 2016)
This article explores the complex relationship between processes of making, memory, healing, and social activism activated by Walking With Our Sisters, a large-scale commemorative installation intended to foster awareness for missing and murdered Indigenous women in Canada.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; art autochtone; art contemporain; artistes autochtones; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; féminicide; féminisme autochtone; histoire de l'art; histoire et politique; militance; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Inné/acquis - Gouyon, Pierre-Henri (Encyclopédie critique du genre, 2016)
Le débat sur l’inné et l’acquis devient particulièrement vif quand il s’applique aux concepts de sexe et genre. L’approche de l’hérédité développée dans le domaine de la génétique permet de distinguer les « effets » des gènes de ceux de l’environnement. Mais cette opposition est beaucoup moins claire que ne le laissent souvent penser les présentations de la génétique. En effet, seules les variations peuvent être étudiées en génétique, et elles sont contingentes par rapport aux individus choisis pour l’étude et aux conditions dans lesquelles ils vivent. Les effets des gènes sont aussi dépendants de ces conditions. Cet article tente de présenter de quelle manière les concepts de la génétique peuvent nourrir les travaux de sciences sociales sur le genre en montrant que la méthodologie de la génétique produit une sorte de boîte noire qui contient tous les facteurs, y compris sociaux, influençant l’« expression » des gènes. On montrera que le difficile dialogue entre génétique et sciences humaines et sociales résulte de différences marquées dans la façon de comprendre ce qui, chez les humains, résulte de l’inné ou de l’acquis.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; discours dominant; europe; france; inégalités; premier cycle; privilèges; pédagogie; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences